1993
DOI: 10.2172/10150408
|View full text |Cite
|
Sign up to set email alerts
|

Area 5 Site Characterization Project: Report of hydraulic property analysis through August 1993

Abstract: Table 2. Standard methods in use by the DRI Water Analysis Laboratory (Rcno, NV). Parameter Standard Method i i pH EPA-600/4-79-020, Method 150.1 Specific Conductance EPA-600/4-79-020, Method 120.1 Alkalinity USGS, Method 1-2030-85 Chloride EPA-600/4-79-020, Method 325.1 Sulfate EPA-600/4-84-O17, Method 300.0 Sodium EPA-600/4-79-020, Method 273.1 Potassium EPA-600/4-79-020, Method 258.1 Calcium EPA-600/4-79-020, Method 215.1 Magnesium EPA-600/4-79-020, Method 242.1 Silica USGS, Method 1-2700-85 Bromide EPA-600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Temperature profiles measured in the PW series wells indicate a local geothermal gradient of 11–14°C km −1 , which fall on the low end of the range of measured geothermal gradients in the Great Basin [ Davisson et al , 1994; Blankennagel and Weir , 1973]. Hydraulic property analyses completed on samples from the 3 boreholes (PW‐1, PW‐2, and PW‐3) that penetrated the entire vadose zone include gravimetric water content, water potential, bulk density, saturated hydraulic conductivity, water retention, porosity and grain size distribution [ Estrella et al , 1993; REECo , 1994]. Table 1 provides a summary of the measured site characteristics, soil properties and hydraulic parameters.…”
Section: Results From the Nevada Test Site Coresmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature profiles measured in the PW series wells indicate a local geothermal gradient of 11–14°C km −1 , which fall on the low end of the range of measured geothermal gradients in the Great Basin [ Davisson et al , 1994; Blankennagel and Weir , 1973]. Hydraulic property analyses completed on samples from the 3 boreholes (PW‐1, PW‐2, and PW‐3) that penetrated the entire vadose zone include gravimetric water content, water potential, bulk density, saturated hydraulic conductivity, water retention, porosity and grain size distribution [ Estrella et al , 1993; REECo , 1994]. Table 1 provides a summary of the measured site characteristics, soil properties and hydraulic parameters.…”
Section: Results From the Nevada Test Site Coresmentioning
confidence: 99%
“…Thus matric potential and water potential are used interchangeably in this discussion. Chloride concentrations were obtained from Estrella et al [1993]. Only data from core samples, as opposed to cuttings, are used in this paper.…”
Section: Results From the Nevada Test Site Coresmentioning
confidence: 99%
See 1 more Smart Citation
“…The values reported in Table 3 used groundwater to prepare the equilibrating solution, which may directly affect the experimental results. Estrella et al, (1993) reported that the ionic strength of the soil solution is much higher than that of the groundwater at Area 5. An increase in ionic strength decreases the thickness of the diffuse double layer ((DDL) -distance over which the solution concentration is affected by the colloid charge), which in turn can affect adsorption.…”
Section: The Values Reported Inmentioning
confidence: 99%
“…At low water content, sorption sites of the inorganic surfaces can effectively sorb organic compounds, however, at high water content, sorption of organic compounds is controlled by soil organic matter. Adsorption of a number of organic and volatile organic compounds (VOCs) has been found to be greater as soil moisture decreases (Hance, 1977;Bailey and White, 1964;Yaron and Saltzman, 1977;Estrella et al, 1993;Steinberg and Kreamer, 1993). Studies have shown that soil water content drastically inhibits vapor-phase sorption given that the solubility of the tested gas in water is low.…”
Section: Factors Affecting Sorptionmentioning
confidence: 99%